White men talking - Grace, Sherrill (Journal of Northern Studies, 2007)
In this essay the author discusses a new play by Canadian playwright Sharon Pollock called Kabloona Talk (2007). The historical context for this contemporary play is the 1914 murders of two Roman Catholic Missionary priests by two Inuit in the Canadian Arctic, followed by two sensational trials held in southern Canada in 1917. Several attempts have been made by writers and scholars to represent what happened and why, but Pollock's play offers a fascinating look at the political manoeuvring that took place behind the scenes as the white lawyers struggled with the conflict between the dictates of European law and the principles guiding the behaviour of a remote group of Inuit about whom white southern Canadians knew next to nothing. Rather than focus on either the murders or the trials, Pollock uses this actual event to explore the timeless issues of justice, and cultural encounter and misunderstanding.